Penerapan Psikoedukasi untuk Meningkatkan Kesadaran dalam Pengelolaan Kecemasan pada Lansia Komunitas Prolanis - Lutviani Hafidah; Rahma Kusumandari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACT The purpose of this study is to examine the effectiveness of a psychoeducation program in improving awareness and anxiety management skills among elderly Prolanis participants at the Posyandu Keluarga community in Kelurahan R and to implement a psychoeducational intervention to reduce anxiety and improve emotional coping. This community-based psychological service aimed to identify mental health issues related to chronic illness and aging, while enhancing participants’ self-awareness and resilience through preventive education at the primary health care level. Materials and Methods. The study employed an experimental method with a Single Group Pretest–Posttest design and a descriptive qualitative approach. Involving interviews, observations, and psychological screening using the Hamilton Anxiety Rating Scale (HARS). Participants consisted of ten older adults aged over 60 years with chronic conditions such as hypertension and diabetes. Data were analyzed using descriptive statistics and paired sample t-tests to assess intervention effectiveness. Results. The findings revealed that most participants experienced anxiety ranging from mild to severe levels. Four participants (40%) demonstrated severe anxiety, primarily related to fears of illness progression and becoming a burden to their families. The psychoeducation sessions which included anxiety awareness, emotional expression, and relaxation techniques such as breathing exercises and the butterfly hug led to a significant improvement in participants’ knowledge and coping abilities. Statistical analysis showed a significant increase in post-test scores (M = 85.00) compared to pre-test scores (M = 69.00; t = -3.361, p = 0.008), confirming the intervention’s effectiveness. Conclusions. Psychoeducational interventions focusing on anxiety management and relaxation skills effectively reduced anxiety symptoms among elderly participants. Strengthening family involvement, empowering community health cadres, and integrating psychological education within Prolanis activities are essential strategies for sustainable mental health care among older adults in community health settings. Keywords: Elderly anxiety, chronic disease, psychoeducation, community intervention, mental health promotion